1991
DOI: 10.1007/bf01973716
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of granulocytic and erythroid progenitor cells are affected differently by short-term, low-level benzene exposure

Abstract: In previous work, we determined that granulocytic (CFU-GM) and erythroid (CFU-E) progenitor cell populations exhibited disparate responses to short-term benzene exposures. We now report on work investigating possible mechanisms for these observed disparate responses. Mice were exposed to either air or 10 ppm benzene for 6 h/d X 5 d. Immediately after the last exposure, mice were injected, i.v., with either saline or hydroxyurea (HU). The dose of HU was sufficient to kill hematopoietic cells in or near S-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…This is in contrast to reports showing 10 ppm benzene induced a decrease in CFU-E counts after 5 days exposure, 6 hr/day, in DBA/2J mice (Dempster and Snyder, 1991) and after 32, 66, and 178 days of exposure, 6 hr/day, in C57BI mice (Baarson et al, 1984). In addition, Baarson et al reported a significant decrease in blood erythrocytes in mice exposed to 10 ppm benzene for 66 and 178 days, whereas in the present study mice exposed to 1 or 10 ppm benzene did not have significant changes in the percentage or number of erythropoietic cell (TER + ) counts, reticulocytes, or erythrocytes.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to reports showing 10 ppm benzene induced a decrease in CFU-E counts after 5 days exposure, 6 hr/day, in DBA/2J mice (Dempster and Snyder, 1991) and after 32, 66, and 178 days of exposure, 6 hr/day, in C57BI mice (Baarson et al, 1984). In addition, Baarson et al reported a significant decrease in blood erythrocytes in mice exposed to 10 ppm benzene for 66 and 178 days, whereas in the present study mice exposed to 1 or 10 ppm benzene did not have significant changes in the percentage or number of erythropoietic cell (TER + ) counts, reticulocytes, or erythrocytes.…”
Section: Discussioncontrasting
confidence: 99%
“…Results of many additional studies of laboratory animals (mainly mice, which are particularly sensitive to benzene hematotoxicity, but also rats and pigs) support findings of benzene-induced effects on bone marrow cellularity (hyper-and/or hypocellularity) and colony-forming stem cells, as well as granulocytic hyperplasia, following repeated acute-, intermediate-, or chronicduration inhalation exposure to benzene vapors at concentrations ranging from 10 to 500 ppm (Baarson and Snyder, 1991;Baarson, et al, 1984;Chertkov, et al, 1992;Corti and Snyder, 1996;Cronkite, et al, 1982Cronkite, et al, , 1985Cronkite, et al, , 1989Dempster and Snyder, 1991;Dow, 1992;Farris, et al, 1993Farris, et al, , 1997bNeun, et al, 1992Neun, et al, , 1994Plappert, et al, 1994a,b;Snyder, et al, 1978aSnyder, et al, , 1980Snyder, et al, , 1982Vacha, et al, 1990). For example, Dempster and Snyder (1991) observed a 50% reduction in CFU-E (erythroid progenitor cells) in bone marrow of DBA/2 mice exposed to 10 ppm benzene for 6 h/ day for 5 days. Farris, et al (1997b) reported benzene-induced decreased numbers of total bone marrow forming cells, progenitor cells, and differentiating hematopoietic cells in mice exposed to benzene vapor concentrations ≥200 ppm, 6 h/ day, 5 days/week for up to 8 weeks.…”
Section: Hematological Effectsmentioning
confidence: 75%
“…For example, Dempster and Snyder (1991) observed a 50% reduction in CFU-E (erythroid progenitor cells) in bone marrow of DBA/2 mice exposed to 10 ppm benzene for 6 h/ day for 5 days. Farris, et al (1997b) reported benzene-induced decreased numbers of total bone marrow forming cells, progenitor cells, and differentiating hematopoietic cells in mice exposed to benzene vapor concentrations ≥200 ppm, 6 h/ day, 5 days/week for up to 8 weeks.…”
Section: Hematological Effectsmentioning
confidence: 95%
“…Chronic exposure to benzene in vivo is associated with the dysregulation of myeloid development, and HQ has been demonstrated to produce similar alterations in myeloid differentiation in vitro (Cronkite et al, 1989;Dempster and Snyder, 1991;Irons et al, 1992;Irons andStillman, 1993, 1996b). Because PU.1 is an important regulator of lineage commitment and a master regulator of myeloid differentiation, HQ-induced alterations in the regulation of the activity of this transcription factor may explain previously observed alterations in early myeloid development following exposure to benzene.…”
Section: Discussionmentioning
confidence: 95%